Enhancement of Mathematics Critical Thinking Skills through Problem Based Learning Assisted with Concrete Media - Pramestika, Ni Putu Dyah; Wulandari, I Gusti Agung Ayu; Sujana, I Wayan (Journal of Education Technology, 2020)
In learning mathematics, students are still found to have difficulty in understanding and developing critical thinking skills. Therefore, the purpose of this study is to determine the significant influence of the Problem Based Learning model assisted by concrete media on the ability to think critically mathematics in grade IV in elementary school. This research was a quasi-experimental study with a non-equivalent control group design. The population of class IV SD as many as 293 people. The sample was determined by cluster random sampling technique. The sample in the experimental group was 32 students and the control group was 30 students. Data used as a test method in the form of a subjective test (description). The data obtained were analyzed using the t-test analysis technique with the polled variance formula. The results of data analysis were obtained (t-count = 4.021> t-table = 2,000) at the significance level of 5% (dk = 32 + 30 - 2 = 67) which means that there was a significant difference in the ability to think critically mathematics between groups being taught with the model of Problem Based Learning with media aids Concretely with the group learned using conventional learning models in class IV elementary school. It can be concluded that the Problem Based Learning model assisted by concrete media influences the ability to think critically mathematics in class IV. The results of this study can be used as input for teachers to choose various learning models in teaching.